RELEVANSI PEMIKIRAN OLIVER SHELDON DALAM PRAKTIK PENDIDIKAN DI SEKOLAH SDN RAWA BUAYA 07 DAN SDN CENGKARENG TIMUR 03 - Tejawiani, Ida; Helmawati; Rahmat, Dwi; Susilawati; Herawati; Masruroh, Iroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relevance of Oliver Sheldon’s educational thought to educational practices at SDN Rawa Buaya 07 and SDN Cengkareng Timur 03, West Jakarta. Oliver Sheldon’s concept of object teaching emphasizes learning through direct observation and concrete experiences, positioning students as active participants in constructing knowledge. This qualitative descriptive study was conducted in two public elementary schools using observation, in-depth interviews, and documentation as data collection techniques. The research participants consisted of principals, teachers, students, and parents selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while data credibility was ensured through source, technique, and time triangulation. The findings indicate that educational practices in both schools have reflected several principles of Oliver Sheldon’s educational philosophy, particularly through the implementation of student-centered learning, collaborative activities, classroom discussions, and the use of various instructional media. However, the implementation of object teaching has not been fully optimized because learning activities are still predominantly supported by visual media such as pictures and videos rather than direct interaction with concrete objects and the surrounding environment. The study also reveals that teacher commitment, school support, adequate learning facilities, and students’ enthusiasm serve as supporting factors, whereas limited instructional time, insufficient concrete learning resources, and the need for continuous teacher professional development remain the primary challenges. Therefore, Oliver Sheldon’s educational thought remains relevant as a philosophical foundation for strengthening contextual, experiential, and meaningful learning practices in contemporary elementary education.